Treatment outcome in dually HIV-1 and HIV-2 coinfected patients living in Spain. (15th November 2019) - Requena, Silvia; Caballero, Estrella; Lozano, Ana Belén; Ríos-Villegas, María José; Benito, Rafael; Rojo, Silvia; Cabezas, Teresa; Macià, María Dolores; Nieto, María del Carmen; Soriano, Vicente; de Mendoza, Carmen
Abstract : Background: Whereas HIV-1 has spread globally, HIV-2 is mainly found in West Africa where dual HIV-1/HIV-2 coinfection is nowadays uncommon. Herein, we report the rate, main characteristics, and treatment outcomes of all dually infected patients living in Spain. Methods: We identified retrospectively all persons coinfected with HIV-1 recorded at the Spanish HIV-2 registry. Dual infection had been confirmed using PCR in plasma and/or cells, and/or using discriminatory serological tests. Results: From a total of 373 individuals with HIV-2 recorded at the Spanish registry, 34 (9.1%) were coinfected with HIV-1. Compared with HIV-2 monoinfected persons, dually infected patients were more often male (67.6%), presented with lower median CD4 + cell counts (204 cells/μl), and had developed more frequently AIDS events (26.5%). Although 61.7% came from West Africa, 6 (17.6%) were native Spaniards. HIV-1 non-B subtypes were recognized in 75% of coinfected patients, being the most prevalent CRF02_AG. At baseline, 45% of dually infected patients had undetectable plasma HIV-2 RNA. After a median follow-up of 32 (13–48) months on antiretroviral therapy, dually infected patients achieved undetectable viremia in 85% for HIV-1, in 80% for HIV-2; and in 70% for both viruses. Median CD4 + cell counts reached up to 418 cells/μl. Conclusion: Roughly 9% of individuals with HIV-2 infection living in Spain are coinfected with HIV-1. Overall, 70% of dually infected patients achieved viral suppression for both viruses under antiretroviral therapy. Given the relatively large population of West Africans living in Spain and the continuous migration flow from HIV-2 endemic areas, HIV-1/HIV-2 coinfection should always be excluded at first diagnosis in all HIV-seroreactive persons.